2009
DOI: 10.1007/s11010-009-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Human β-galactoside α-2,3-sialyltransferase (ST3Gal III) attenuated Taxol-induced apoptosis in ovarian cancer cells by downregulating caspase-8 activity

Abstract: Taxol triggers apoptosis in a variety of cancer cells, but it also upregulates cytoprotective proteins and/or pathways that compromise its therapeutic efficacy. In this report, we found that Taxol treatment resulted in caspase-8-dependent apoptosis in SKOV3 human ovarian cancer cells. Moreover, Taxol-induced apoptosis was associated with caspase-3 activation. Interestingly, Taxol treatment upregulated α-2,3-sialyltransferase (ST3Gal III) expression and forced expression of ST3Gal III attenuated Taxol-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…We have found that Taxol at 100 – 500 nM induces robust apoptosis in cell lines from different types of cancer [22]. As shown in Figure 1(a), the annexin V binding assay revealed that Taxol at 100 nM induced early apop tosis in 28% of SKOV3 cells, and RT-PCR analysis showed that while SKOV3 cells express little GM3 synthase at the mRNA level, it was significantly increased after Taxol treatment (Figure 1(b)).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have found that Taxol at 100 – 500 nM induces robust apoptosis in cell lines from different types of cancer [22]. As shown in Figure 1(a), the annexin V binding assay revealed that Taxol at 100 nM induced early apop tosis in 28% of SKOV3 cells, and RT-PCR analysis showed that while SKOV3 cells express little GM3 synthase at the mRNA level, it was significantly increased after Taxol treatment (Figure 1(b)).…”
Section: Resultsmentioning
confidence: 96%
“…Our previous results showed that Taxol-induced apoptosis in SKOV3 ovarian cancer cells is associated with caspase-8, -9, and -3 activation in these cells [22]. Despite cytoreductive surgery and primary chemotherapy, advanced epithelial ovarian cancer is a highly lethal malignancy [23].…”
Section: Discussionmentioning
confidence: 99%
“…22 Sialyltransferases participates of many biological processes, including cell-cell communication, cell-matrix interaction, adhesion, and protein targeting. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The ST family consists of three subfamilies with 20 anabolic enzymes [12], namely, α2,3-sialyltransferases that mediate the transfer of sialic acid with an α2,3-linkage to terminal Gal residues (ST3GalI-VI) and α2,6-sialyltransferases that mediate the transfer of sialic acid with an α2,6-linkage to terminal Gal (ST6GalI-II) or GalNAc residues (ST6GalNAcI-VI) [13, 14]. The link between the ST family and EOC was reported previously by few studies [1517]. For example, Christie et al reported that sialylation of β1 integrins mediated by ST6Gal-I altered the adhesion and migration characteristics of ovarian cancer cells through the extracellular matrix leading to peritoneal metastasis [17].…”
Section: Introductionmentioning
confidence: 95%